2019
DOI: 10.1080/09168451.2019.1659717
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of the effect of oral supplementation of Lactobacillus plantarum strain SNK12 on mRNA levels of neurotrophic factors and GABA receptors in the hippocampus of mice under stress-free and sub-chronic mild social defeat-stressing conditions

Abstract: The effect of Lactobacillus plantarum SNK12 (CPLP) supplementation on mRNA levels of hippocampal neurotrophic factors and gamma aminobutyric acid receptors (GABAR) was tested. In Experiment 1, stress-free, unsupplemented and CPLP (4 × 108 cells/head)-supplemented male C57BL/6J (B6) mice were the experimental animals. In Experiment 2, intruder (male, B6) mice [negative control; unsupplemented, sub-chronic mild social defeat stress (sCSDS)-induced; and CPLP-supplemented, sCSDS-induced] were exposed to aggressor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…factors associated the development of mood disorders (38). It was found that sCSDS did not affect BDNF, NGF, NT-3, NtrkA, and NtrkB gene expres- sCSDS mice in the social interaction test was affected by several environmental factors, including feed (17).…”
Section: Biochemical Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…factors associated the development of mood disorders (38). It was found that sCSDS did not affect BDNF, NGF, NT-3, NtrkA, and NtrkB gene expres- sCSDS mice in the social interaction test was affected by several environmental factors, including feed (17).…”
Section: Biochemical Analysismentioning
confidence: 97%
“…Studies employing experimental animals have shown that administering specific probiotics eases stress-induced glucocorticoid and inflammatory cytokine responses in conjunction with decrease in depression-and anxiety-related behaviors (4,7,15). Dietary supplements of Lactobacillus have been found to increase psychosocial stress resilience in sCSDS mice (23) and gene expression of neurotrophic factors such as brain-derived neurotrophic factor (BDNF) in the hippocampus (38). Moreover, patients with major depression were found to have lower Bifidobacterium and Lactobacillus counts in their gut than healthy controls did (1).…”
mentioning
confidence: 99%
“…The methods employed for PCR analysis were the same as those previously described. (17,18) Statistical analysis. To estimate significant differences in TUNEL-positive cell numbers and the relative gene expression between groups, two-way analysis of variance (ANOVA; factors UV radiation and EBNE supplementation) and Tukey-Kramer post hoc comparisons were used.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…In the present study, to assess the habituation abilities of the experimental mice, an open-field arena was used (500 × 500 × 400 mm; O'Hara & Co., Tokyo, Japan). The habituation test procedure was as that previously described [12]. The total distance (cm/600 s) traveled by mice was measured by TimeOFCR1 software (O'Hara & Co.) on days 0, 14, and 21, and the habituation score (%) was calculated as 100 × (moving distance on day 14 or 21)/(moving distance on day 0).…”
Section: Habituation Testmentioning
confidence: 99%
“…Optimal primers and probes were designed using freely available online tools (https://www.rocheapplied-science.com/) or selected from Bioresearch Technologies Japan (Tokyo, Japan). The methods employed for PCR analysis were the same as those previously described [12]. All genes analyzed for mRNA levels are also listed in Table 1.…”
Section: Measurement Of Gene Expression In Hippocampusmentioning
confidence: 99%